Understanding Brands - Peter Cheverton (Kogan Page Limited, 2006)
A good brand will make you feel good about the choice you have made, to buy it and to use it. A good brand will help you make that choice in the first place, and it can do that because it knows how to make you feel good. The good brand, as illustrated in Figure PI.1 (see page 2), is a virtuous circle of action and reaction, give and take. That it can do all these things shows what a complex thing a brand is. Much more than a name and a slogan, and substantially more than an advertisement – these things are but window dressing compared to the heart of a brand. The heart of the brand is an idea, and ideas can change, and be changed – that’s how a brand lives, learns and grows.